Digitalisasi dalam UMKM Anak Muda: Pelaporan Keuangan dengan Aplikasi - Nirwana, Ros; Marliadi, Reny; Rukman, Rukman (Universitas Nusantara PGRI Kediri, 2025)
Digital technology is currently widely used to improve the accuracy, effectiveness, and efficiency of operations in a business/enterprise, both large and small, micro, or medium scale. Financial reporting in MSMEs often only uses simple recording methods and is carried out conventionally. The use of technology in this case is limited to calculating addition, subtraction, multiplication, or division using a calculator while the recording system is carried out traditionally. This community service (PkM) activity is focused on direct assistance and guidance with simulation and participatory methods for MSME Eatspot.id to create accountable financial reporting based on technology. The results of PkM concluded that MSME Eatspot.id has been able to manage and report finances by utilizing technology independently. MSME Eatspot.id partners have been able to implement the transfer of knowledge received regarding the use of the Akuntansiku application